Early Cytokine-Induced Transient NOX2 Activity Is ER Stress-Dependent and Impacts β-Cell Function and Survival - Eloisa A. Vilas-Boas; Christopher Carlein; Lisa Nalbach; Davidson C. Almeida; Emmanuel Ampofo; Angelo R. Carpinelli; Leticia P. Roma; Fernanda Ortis (MDPI AG, 2021)
In type 1 diabetes (T1D) development, proinflammatory cytokines (PIC) released by immune cells lead to increased reactive oxygen species (ROS) production in β-cells. Nonetheless, the temporality of the events triggered and the role of different ROS sources remain unclear. Isolated islets from C57BL/6J wild-type (WT), NOX1 KO and NOX2 KO mice were exposed to a PIC combination. We show that cytokines increase O2•− production after 2 h in WT and NOX1 KO but not in NOX2 KO islets. Using transgenic mice constitutively expressing a genetically encoded compartment specific H2O2 sensor, we show, for the first time, a transient increase of cytosolic/nuclear H2O2 in islet cells between 4 and 5 h during cytokine exposure. The H2O2 increase coincides with the intracellular NAD(P)H decrease and is absent in NOX2 KO islets. NOX2 KO confers better glucose tolerance and protects against cytokine-induced islet secretory dysfunction and death. However, NOX2 absence does not counteract the cytokine effects in ER Ca2+ depletion, Store-Operated Calcium Entry (SOCE) increase and ER stress. Instead, the activation of ER stress precedes H2O2 production. As early NOX2-driven ROS production impacts β-cells' function and survival during insulitis, NOX2 might be a potential target for designing therapies against early β-cell dysfunction in the context of T1D onset.